cymyc: Calabi-Yau Metrics, Yukawas, and Curvature - Giorgi Butbaia; Damián Mayorga Peña; Justin Tan; Per Berglund; Tristan Hübsch; Vishnu Jejjala; Challenger Mishra (Journal of High Energy Physics)
Abstract We introduce cymyc, a high-performance Python library for numerical investigation of the geometry of a large class of string compactification manifolds and their associated moduli spaces. We develop a well-defined geometric ansatz to numerically model tensor fields of arbitrary degree on a large class of Calabi-Yau manifolds. cymyc includes a machine learning component which incorporates this ansatz to model tensor fields of interest on these spaces by finding an approximate solution to the system of partial differential equations they should satisfy.